From the Margins to Protection:Empowerment of Marginalized Communities for Exploited Children - Indah Sri Utari (Faculty of Law, Universitas Negeri Semarang, 2024)
Economic exploitation of children is a form of human rights violation that is still rampant, especially in areas with high poverty rates and limited access to education and legal protection. In Central Java, this phenomenon often affects children from marginalized families who are forced to work to help support their families' economy. This study aims to analyze how empowering marginalized communities can be an effective strategy in supporting the implementation of legal protection for children who are victims of economic exploitation. Using a qualitative approach and case study methods in several areas in Central Java, this study explores the role of local communities, civil society organizations, and government institutions in building legal awareness and social capacity of marginalized communities. The results of the study show that community empowerment not only increases understanding of children's rights but also strengthens the community's bargaining position in rejecting exploitative practices. Programs such as skills training, legal counseling, and the formation of local advocacy groups have been shown to create a more protective environment for children. In addition, collaboration between the community, local government, and child protection institutions is key to building a sustainable protection system that is responsive to local needs. This study confirms that a community-based approach is an important element in child protection strategies, especially in areas with limited resources. Therefore, policies are needed that support the active participation of marginalized communities in the process of formulating and implementing child legal protection. Thus, child protection efforts are not only the responsibility of the state, but also become a collective movement from the grassroots that starts from shared awareness and concern.